(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The Wreck of the Deutschland was Hopkins’s,‘first major poem written in ‘sprung rhythm’. Herein is contained a brief analysis of this heart moving poem and theimpact it has created in the minds of many readers down the ages. The authorsin the opening paragraphs of this article have made a concerted attempt tobring out some parallelism from the Book of Psalms and also the theologicalaspect of innocent suffering. Thisconcept of human suffering seems deeply embedded in this particular poem ofHopkins and this is what the authors wish to portray for their readers. We have also highlighted the various aspectsof the three streams of suffering that Hopkins talks about in this epicpoem. The three sufferings are broughtout in this manner, Hopkins own suffering at conversion, the suffering of theship wrecked people especially the nuns on the ship and finally delving intothe sufferings of Christ. God thesupreme who is good and wishes that good also takes place in the lives of humanbeings and at the same allows us to suffer is a persistent curiosity arising inthe minds of all humankind. And this iswhat forms one of the many crucial cruxes into the deeper understanding of thetheology of Christianity. Going onfurther the authors have brought to the attention of the readers, the juxtapostioningdone by Hopkins regarding this concept of human suffering versus the travailsexperienced of the nuns in the ship wreck. In connection to this discourseHopkins mentions and brings into picture the deeply revered catholic saint andspiritual personality Fr. St. Francis as a type of Christ to drive home thisaspect of innocent suffering. Finallytowards the end of this article we wish to focus on the plight of the nuns.